Liquid pump-enabled hydrogen refueling system for heavy duty fuel cell vehicles: Pump performance and J2601-compliant fills with precooling. (18th June 2021) - Li, Jimmy; Ramteke, Ashwin; Youn, Edward; Hansen, Erik; Kratschmar, Kenneth; Prakash, Alvin; Stager, Jerad; Ku, Anthony Y.
Abstract: We have developed a hydrogen (H2 ) refueling solution capable of delivering precooled, compressed gaseous hydrogen for heavy duty vehicle (HDV) refueling applications. The system uses a submerged pump to deliver pressurized liquid H2 from a cryogenic storage tank to a dispensing control loop that vaporizes the liquid and adjusts the pressure and temperature of the resulting gas to enable refueling at 35 MPa and temperatures as low as −40 °C. A full-scale mobile refueler was fabricated and tested over a 6-month campaign to validate its performance. We report results from tests involving a total of 9000 kg of liquid H2 pumped and 1350 filling cycles over a range of conditions. Notably, the system was able to repeatably complete multiple, back-to-back 30 kg filling cycles in under 6 min each, in full compliance with the SAE J2601-2 standard, demonstrating its potential for rapid-throughput HDV refueling applications. Graphical abstract: Image 1 Highlights: A liquid H2 pump-enabled solution for 35 MPa hydrogen refueling has been developed. Results from field testing of a full-scale mobile trailer system are reported. Pump performance: 40 MPa outlet pressure; up to 285 kg/h; 43, 000 pump strokes. System performance: 1350 J2601-2 compliant fill cycles, including back-to-back fills.